The effect of the effectiveness of red ginger and L14 acupressure on (Primary Dysmenorrhoea) in fourth semester students of D III Midwifery Study Program STIKES Maranatha Kupang - Manek, Brigita Dina; Nurul Ilma, Nabilah; Pili Mangngi, Atalia; M.T Duka, Maria; P. Gusman, Avelina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Menstrual pain is commonly felt by women on the first day of menstruation. Based on the results of an initial survey conducted at STIKes Maranatha Kupang D-III Midwifery Study Program 1 (10%) people who experience mild dysmenorrhoea, 7 (70%) people experience moderate dysmenorrhoea, 2 (20%) people who experience severe dysmenorrhoea, 2 (20%) people who experience very severe dysmenorrhoea every month. Objectives : The purpose of this study was to determine the difference in effectiveness between red ginger and L14 acupressure on menstrual pain (primary dysmenorrhoea) in students at STIKes Maranatha Kupang D III Midwifery Study Program.Methods: The design used in this study was comparative analytics with an observational approach. The study population was all adolescent girls who had primary dysmenorrhoea and were not taking painkillers. A sample of 32 respondents was taken by accidental sampling. The instrument used is the NRS Bourbanis pain scale assessment sheet. This research was conducted at STIKes Maranatha Kupang Midwifery Study Program D-III.  Results : The pretest results of the red ginger group showed that most respondents (56%) 9 respondents experienced mild. pain, while the post test results showed almost all respondents (81%) 13 respondents experienced mild pain. The pretest results of the L14 Acupressure group showed that most respondents (75%) 12 respondents experienced moderate pain, while the post test results showed almost all respondents (81%) 13 respondents experienced mild pain. With the statistical test Mann-Whitney Test the results show P_value = 0.030 < (α) 0.05.Conclusions: That there is a significant difference in effectiveness between after consumption of red ginger and L14 on the intensity of menstrual pain in adolescent girls at STIKes Maranatha Kupang Study Program D-III Midwifery. It is hoped that the results of this study can be used as an alternative option to overcome / reduce the intensity of menstrual pain (primary dysmenorrhoea) in adolescent girls without having to use chemical drugs.